SATU SENYAWA STEROID DARI KULIT BATANG TUMBUHAN PALIASA (Kleinhovia hospita L.) ASAL SULAWESI SELATAN - Gaffar, Imran; Mamahit, Lexie P. (Sam Ratulangi University, 2010)
The study aims to isolate and identify the metabolite structure of Kleinhovia hospital L. To achieve the purpose,and extraction of bark with methanol was performed. This extract was partitioned into several organic solutions:n- hexane, chloroform, and ethyl acetate. The partitioned were fractioned and purified by means of severalappropriate methods like liquid vacuum chromatography and pressure column chromatography, and meltingpoint determination. To determine the chemical structure of the isolate, a combination of several spectroscopicmethods, such as infrared (IR), nuclear magnetic resonance (NMR), and advanced NMR technique (HMQC,HMBC and COSY). Result of this research shown that one major constituent was isolated from bark: bï€-sitosterol.